Mediation as an amicable and peaceful means of resolving international disputes in law and Islamic law - Alzahrani, Jamaan Muidh (Journal of Economic, Administrative and Legal Sciences, 2022)
The topic of the research is of high importance, as it shows that mediation is the alternative idea of ​​coercion, violence and the carrying of arms that arise between the conflicting countries, and that it is the duty of the international community To strive to put in place an appropriate framework for this method to codify it and apply it quickly and flexibly to resolve conflict between states; It is more effective in resolving disputes; Because it is a means of international dialogue, less expensive, more flexible, private and confidential. The nature of the research necessitated dividing it into an introduction, in which the researcher explained the subject of this research and the research plan. In the first topic, the definition of international law and conflict, and the jurisprudential criteria for distinguishing between legal and political disputes, then the researcher explained the role of the United Nations in resolving international disputes by peaceful means, and the means adopted by the League of Arab States in resolving Arab conflicts and its role in that, with mentioning the legal formulation It has adopted the principle of settlement, then the researcher mentioned some Arab disputes. Then the researcher explained in the second topic: the definition of mediation, its forms, its characteristics and advantages, the characteristics of the mediator, and the difference between it and arbitration. In the third topic, the researcher explained both reconciliation and mediation in Islamic Sharia and the importance and virtue of reconciliation and Islam’s respect for covenants and covenants. In the fourth topic, a comparison was made between mediation and conciliation in law and Islamic law, and then the research concluded with a conclusion in which some results were recorded. One of the most important results of this research: that conflicts are permanent and continuous, and as countries move and seek their interests, disputes occur, so it is necessary to adapt, control and define them disciplined until contained and resolved through mediation. Among the most important recommendations: the formulation of an independent and integrated law regulating the means of mediation, and putting it into practice, and that the countries of the world, especially the Islamic and Arab countries, must play their role in resolving disputes, as Islam commands us to pay attention to human interests and make them the first of its goals, and Islam is a law to be followed- such as loyalty The Covenant- and a way out for these countries from these and other conflicts.
Keywords: mediation; amicable means; peaceful means; international disputes